Operacional financial management at the Pinar del Rio poultry company, Cuba (Costos y Gestión, 2022)
The research is based on a theoretical and methodological basis with elements of financial analysis, financial planning and working capital management, to justify the characterization of the entity and the support of the planning processes and complete the operating budgets, to analyze the results of short-term business operations and transactions. Ensuring better decision-making in the current economic situation of the organization, strengthening the monthly and annual reports obtained from the investigation, with the aim of making projections and scenarios to achieve optimal results.Achieved through the use of a set of techniques, methods and instruments related to management processes, from the method of simple ratios, evolution of operating cycles, cash and calculation of the optimal cash balance, for the analysis of changes in the collection policy, its feasibility and projection of the financial statements. To have timely and reliable financial information through financial indicators and take corrective measures to minimize risks and obtain real results on the financial situation, in order to control the management of each part that makes up the company.
Keywords: financial statements; working capital; operational financial management; financial planning; financial ratios